Cenizas : Poems - Guardado, Cynthia, 1984- (Book collections on Project MUSE., 2022)
"Cenizas is centered around one Salvadoran family's experiences with grief and identity as it relates to a homeland that only exists in the "in-between"- the place where all the diaspora people exist. The book argues that the Salvadoran Civil War permanently altered the Salvadoran people's reality by forcing them to become refugees that continue to leave their homeland even decades after the war"--